Some clinical and laboratory studies of large pituitary tumours treated with dopamine agonists - Bevan, John Stuart (The University of Edinburgh, 1988)
The patient with a large pituitary tumour presents a number of management problems and conventional treatment with surgery and radiotherapy is unsatisfactory. Reports between 1978 and 1982 showed that some tumours regress during dopamine agonist (DA) therapy, though thiB does not produce a permanent cure (Chapter 1). The aim of the present work was to clarify the effect of DA therapy on different types of large pituitary tumour and to characterise cells from both responsive and unresponsive tumours. Three conclusions resulted from the clinical studies (Chapter 2): (1) Most macroprolactinomas shrink during DA therapy but the shrinkage is often asymmetrical and results in fibrosis during long-term therapy, both of which hamper subsequent surgery. (2) Disconnection hyperprolactinaemia may be considerable and lead to inappropriate DA therapy for non-adenomatous lesions. (3) Non-functioning tumours do not regress during DA therapy. Tumour cells were characterised by tumour cell perifusion (methods described in Chapters 3 and 4), dopamine receptor measurement using [ H]spiperone as radioligand (methods described in Chapter 5) and immunocytochemistry. Prolactin secretion rates from bromocriptinetreated macroprolactinomas were greatly reduced compared with untreated tumours. Most prolactinomas showed dose-related inhibition of prolactin secretion by dopamine and bromocriptine but one tumour was partially bromocriptine resistant in-vivo and in-vitro (Chapter 6). Fifty percent of the non-functioning tumours did not contain, secrete or immunostain for any known anterior pituitary peptide. The remainder secreted small amounts of gonadotrophins or alpha subunit, but the secretion was not inhibited by dopamine, immunostaining was confined to <102! of cells and tumour contents were low (Chapter 7). Despite their failure to regress during bromocriptine treatment, non¬ functioning tumours were shown to possess similar dopamine receptors to prolactinomas and normal anterior pituitary (Chapter 8). Using a novel immunoassay, bromocriptine was shown to be bound to non-functioning tumour dopamine receptors in-vivo. In contrast, two TSH-secreting adenomas were also unresponsive to dopaminergic manipulation but lacked membrane-bound dopamine receptors (Chapter 9). From these results, future clinical practice demands greater care in selecting patients for dopamine agonist or surgical treatments. The finding of dopamine receptors in non-functioning tumours suggests future research on these enigmatic tumours aimed at defining the cell type represented and post-dopamine receptor mechanisms (Chapter 10).